Distribution of glycerol dialkyl glycerol tetraether (GDGT) lipids in a hypersaline lake system. (September 2016) - Li, Jingjing; Pancost, Richard D.; Naafs, B. David A.; Yang, Huan; Zhao, Cheng; Xie, Shucheng
Highlights: Iso- and brGDGTs occur in sediments and soils from the Chaka Salt Lake system. Low cren/cren regioisomer suggests derivation from surrounding alkaline soil. This argues against use of TEX86 in this system. Additional source of brGDGTs for lake and river sediments, in situ or contribution from upland soils. Abstract: Isoprenoid glycerol dialkyl glycerol tetraethers (isoGDGTs) of archaeal origin and branched (br)GDGTs of bacterial origin occur in a diverse range of lacustrine sedimentary environments. They have attracted attention as potential temperature proxies, providing high resolution (palaeo)environmental reconstruction from continental interiors. For this study, the distribution of GDGTs in, and application of GDGT-based proxies to, surface samples from Chaka Salt Lake (China), as well as soils and in-flow river sediments, were investigated to assess whether GDGT-based proxies were applicable to this hypersaline lake system. We show that iso- and brGDGTs were present in all sediments and soils from the Chaka Salt Lake system. GDGT-0 and crenarchaeol were generally the two most abundant isoGDGTs, suggesting Thaumarchaeota as a major biological source of isoGDGTs. The low ratio of crenarchaeol/crenarchaeol regioisomer suggests that Thaumarchaeota of the lake sediments is likely Thaumarchaeota group I.1b derived from the surrounding alkaline soils, arguing against the use of the TEX86 proxy in this system. Because alkaline soils generally have high isoGDGT concentrations, it is likely that a large allochthonous input of isoGDGTs would be a pervasive challenge to palaeoclimate applications in such settings. On the other hand, the brGDGT distributions in the lake and river sediments differed markedly from those in the surrounding soils, suggesting that, instead of deriving from the surrounding soils, at least part of the brGDGTs is synthesized in situ or delivered from more distal upland soils. Taken together, our results indicate that the mixed sources of GDGTs in Chaka Salt Lake complicate the application of GDGT-based proxies, and it will be challenging to use such proxies in this system.